A signaling molecule from intratumor bacteria promotes trastuzumab resistance in breast cancer cells - Gege Qin; Xiying Shao; Xiaolong Liu; Jiachao Xu; Xiaojia Wang; Wenxi Wang; Lu Gao; Yuxin Liang; Lina Xie; Dan Su; Hongwei Yang; Wei Zhou; et al. (Proceedings of the National Academy of Sciences, 2025)
Emerging evidence indicates that intratumor bacteria exist as an active and specific tumor component in many tumor types beyond digestive and respiratory tumors. However, the biological impact and responsible molecules of such local bacteria–tumor direct interaction on cancer therapeutic response remain poorly understood. Trastuzumab is among the most commonly used drugs targeting the receptor tyrosine-protein kinase erbB-2 (ErbB2) in breast cancer, but its resistance is inevitable, severely limiting its clinical effectiveness. Here, we demonstrate that the quorum-sensing signaling molecule N-(3-oxo-dodecanoyl) homoserine lactone (3oc), a chemical compound released by Pseudomonas aeruginosa ( P. aeruginosa ), one tumor-resident bacteria with a relative high abundance in breast cancer, promotes breast cancer cell resistance to trastuzumab. Mechanically, 3oc directly leads to spontaneous dimerization of the transforming growth factor β (TGF-β) type II serine/threonine kinase receptor on the cell membrane in a ligand-independent manner. The 3oc-induced TGF-β signaling subsequently triggers ErbB2 phosphorylation and its downstream target activation, overcoming the inhibition effect of trastuzumab on ErbB2. With specific real-time qPCR, fluorescence in situ hybridization imaging, and liquid chromatography ionization tandem mass spectrometry analyses of clinical samples, we confirmed that P. aeruginosa and its signaling molecule 3oc exist in breast cancer tissues and there is a clinical correlation between P. aeruginosa colonization and trastuzumab resistance. This work expands the biological functions of intratumor bacteria in cancer treatment responsiveness and provides a unique perspective for overcoming trastuzumab resistance.